The Educational Process of the Work-integrated Learning (WIL) program: Case Study of Engineering Faculty, Rajamangala University of Technology Lanna, Thailand - Nuangpirom, Pinit; Jewpanya, Parida; Pitjamit, Siwasit; Jaichomphu, Pakpoom; Chaithanu, Kitchar (Journal of Technical Education and Training, 2023)
This research studies the educational process of the Work-integrated Learning (WIL) program in a case study of engineering faculty, at Rajamangala University of Technology Lanna (RMUTL), Thailand. The opinions of students and teachers who participated in the WIL program are investigated. In this regard, during the academic year 2020-2022, we applied for the "The Questionnaire about the Educational Process in WIL program". The questionnaire was sent to a sample of 120 students and 50 teachers. The subjects answered to questions regarding the roles of students, teachers, factory trainers, the quality of curricula, the effectiveness of teaching methods, the establishment, and university and executive support, in the WIL program. The conducted study shows the necessity of developing WIL curricula and strengthening a modern WIL learning process. WIL had an impact on students’ increased responsibility and organizational communication. Teachers and factory trainers were obliged to have integrated performance of their teaching skills. New courses should be created expressly for WIL to reduce study time and interact with the workplace. The WIL model should also be improved student learning effectiveness. To effectively handle and administer the project with the backing of the executive’s policy, the administrative framework and structure should be established.